STRUCTURAL FEATURES OF THE DEEP STRUCTURE OF THE SOUTHEASTERN YANA-KOLYMA FOLD SYSTEM FROM COMPLEX GEOPHYSICAL DATA - N. K. Gayday; N. A. Goryachev; I. M. Khasanov; E. Yu. Goshko (Геодинамика и тектонофизика)
Ore deposits of the Magadan region are now in the focus of comprehensive studies as information on their deep structure is needed for both subsoil prospecting and regional development planning. This article presents the research results for the southeastern flank of the Yana-Kolyma orogenic belt. This area located at the junction with the Okhotsk-Koryak orogenic belt was investigated using the northeastern segment of the regional geophysical profile 3-DV. We analyzed the frequency-energy sections of the crust along the profile, 3D crustal density model of the entire study area, and magnetic, geoelectric and gravimagnetic characteristics of the crust. Complex data interpretation allowed tracing the crustal fault zones, areas wherein the crust material was strongly reworked, and zones of quasi-horizontal stratification. Considering the revealed features of the physical parameters of the crust material, we conclude that the currently accepted boundaries of individual tectonic blocks in the study area need to be adjusted. The northern boundary of the Balygychan uplift should be mapped along the Pautov fault. The Srednekansky branch of the Inyali-Debinsky synclinorium should be considered a transitional block that belongs to the Sugoi synclinorium, and its name should be changed to the Orotukan block.